2013
DOI: 10.1016/j.ijid.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of dengue fever in Khyber Pakhtunkhawa, Pakistan

Abstract: The results of the present cohort study of febrile subjects show that young people and males are more susceptible to dengue fever. Dengue infection was most prominent in the post-monsoon season, in urban areas, and in patients with a history of travel to an endemic locality. Furthermore seven deaths were found in our cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 24 publications
21
23
1
Order By: Relevance
“…The study population consisted of more males than females and is consistent with the studies done elsewhere and in Sri Lanka [Gupta et al, ; Messer et al, ; Ali et al, ]. In Sri Lanka, hospitalized patients reference to DENV infections, show males seeking hospital treatment whereas females seek care from traditional practitioners and are less likely to present to hospitals due to factors such as family commitments [Guha‐Sapir and Schimmer, ].…”
Section: Discussionsupporting
confidence: 77%
“…The study population consisted of more males than females and is consistent with the studies done elsewhere and in Sri Lanka [Gupta et al, ; Messer et al, ; Ali et al, ]. In Sri Lanka, hospitalized patients reference to DENV infections, show males seeking hospital treatment whereas females seek care from traditional practitioners and are less likely to present to hospitals due to factors such as family commitments [Guha‐Sapir and Schimmer, ].…”
Section: Discussionsupporting
confidence: 77%
“…Demographic data analysis showed that the infection rate in males was double the rate in females, with a male to female ratio of 2:1, an observation that corresponds with previous results from studies of the KPK province [1213]. …”
supporting
confidence: 87%
“…During 2013 to 2015, individuals aged 16-30 yr of age were the main victims of DENV infection, followed by individuals between 31-45 yr of age [112]. Demographic data analysis showed that the infection rate in males was double the rate in females, with a male to female ratio of 2:1, an observation that corresponds with previous results from studies of the KPK province [1213].…”
supporting
confidence: 74%
“…Additionally seroprevalence surveys sometimes use serum samples collected for a different purpose and therefore may not be representative of the population. Six out of the 37 studies used such samples: from blood banks [44], ante-natal clinics [64], hospitals [55,79,80], or residual samples from a different study [66]. Use of convenience samples can increase the volume of serological data produced, but the potential biases such sampling introduces must be taken into account when analysing such data.…”
Section: Discussionmentioning
confidence: 99%